Ternary composite nickel-based difunctional electrocatalyst as well as preparation method and application thereof

The Co4S3/Co(OH)2/Ni3Se2/NF catalyst synthesized by hydrothermal and electrochemical methods solves the problem of the material clusters and active sites covered in the electrocatalytic reaction of nickel-based catalysts, and achieves efficient sulfur ion oxidation and hydrogen evolution reactions.

CN119710804AActive Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411889285.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing nickel-based catalysts have the problem of material clusters and active sites being covered in electrocatalytic reactions, which leads to poor electron transfer and mass transfer, and it is difficult for traditional hydrothermal methods to form ternary heterogeneous interfaces, affecting electrocatalytic activity.

Method used

The ternary composite nickel-based bifunctional electrocatalyst of Co4S3/Co(OH)2/Ni3Se2/NF was synthesized by hydrothermal method combined with electrochemical method. The structure and active sites of the catalyst were optimized using layer-by-layer structural design and fine regulation of electrochemical vulcanization.

Benefits of technology

The electrocatalytic activity of the catalyst is significantly improved, the reaction kinetics is enhanced, and the energy input of the electrocatalytic reaction is reduced, achieving more efficient sulfur ion oxidation and hydrogen evolution reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710804A_ABST
    Figure CN119710804A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalysis, and particularly relates to a ternary composite nickel-based difunctional electrocatalyst and a preparation method and application thereof. The preparation method of the electrocatalyst comprises the following steps: pretreatment of foamed nickel, hydrothermal synthesis of Ni3Se2 / NF, hydrothermal synthesis of Co (OH) 2 / Ni3Se2 / NF, and electrochemical treatment. According to the preparation method disclosed by the invention, two-step hydrothermal and electrochemical vulcanization regulation and control are utilized to finely regulate and control in-situ growth of multi-component components, so that effective compounding of multi-phase heterogeneous components is realized, interface electron rearrangement is enhanced, and the electrocatalytic activity of the catalyst is effectively improved; the prepared electrocatalyst has a multi-layer structure, outer-layer sulfide components effectively wrap inner-layer active substances, effective compatibility of different active sites is achieved, the inner-layer active substances are protected from being destroyed in the electrocatalytic process, the material structure is stable, and the catalyst has multiple heterogeneous interfaces, finely-modulated active centers and excellent electrocatalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and specifically relates to a ternary composite nickel-based bifunctional electrocatalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen (H2) has attracted widespread attention due to its significant energy density and environmentally friendly properties. Among the many hydrogen production technologies, electrocatalytic alkaline water hydrogen production technology is mature, low-carbon and environmentally friendly, and has great development prospects. However, its slow oxygen evolution (OER) reaction at the anode greatly limits its development. Therefore, the use of the kinetically faster sulfur ion oxidation reaction (SOR) to assist the hydrogen evolution reaction (HER) has become a powerful strategy to overcome this obstacle. With the worsening of environmental pollution and energy crisis, the development of bifunctional SOR / / HER electrocatalysts with excellent electrocatalytic activity has become a prerequisite for realizing the above-mentioned sulfur ion oxidation-assisted energy-saving hydrogen production technology.

[0003] In recent years, a lot of work has been done on the development of efficient non-precious electrocatalysts. Among these candidate materials, nickel-based catalysts have attracted much attention due to their strong interfacial effects and unique electronic structures. 2- As a soft base, it prefers to react with the "soft acid" Ni 2+ site binding; on the other hand, in some nickel-based complexes, there are also Ni as hard acid sites. 3+ , this site exhibits a soft and hard repulsion effect with the soft base product in SOR, and is more likely to construct a sulfur-phobic interface. The above unique properties not only make the nickel-based catalyst have better responsiveness in the SOR reaction, but also enable the rapid desorption of insulating sulfur products. Due to the different reaction mechanisms of different reactions, the design and preparation of bifunctional nickel-based electrocatalysts with compatible different catalytic active sites are still difficult. For example, Feng et al. modified Ni3Se2 by introducing metal cation V to increase its surface active sites to optimize the electrocatalytic activity (DOI: 10.1021 / acssuschemeng.1c04695); Shi et al. prepared V-doped Ni3Se2 with a MOF structure and improved the electrocatalytic activity through MOF-derived 3D layered nanostructures (DOI: 10.1016 / j.ijhydene.2020.12.192).

[0004] Different from the above-mentioned method of optimizing the structure of the nickel-based catalyst itself or loading other cations to optimize it, the present invention synthesizes a Co4S3 / Co(OH)2 / Ni3Se2 / NF catalyst by a novel strategy. The catalyst can improve its intrinsic electrocatalytic activity due to the presence of a multiphase heterogeneous structure of Co4S3, Co(OH)2 and Ni3Se2. The present invention solves the common problems existing in existing nickel-based catalysts through a new synthesis route:

[0005] (1) Due to the large differences in the structures of multiphase components, it is often difficult to form a multi-component heterogeneous structure, which is not conducive to the effective rearrangement of electrons and it is difficult to improve its electrocatalytic activity;

[0006] (2) The traditional hydrothermal method for constructing multi-component heterogeneous structures cannot finely regulate the structure and crystallinity of the catalyst. The hydrothermal process is uncontrollable, which is not conducive to the formation of ternary heterogeneous interfaces.

[0007] (3) In the past, nickel-based electrocatalysts often had common problems such as material clustering and covered active sites, which were not conducive to electron transfer and mass transfer during the electrocatalytic reaction. Summary of the invention

[0008] In order to solve the above technical problems, the present invention constructs a ternary composite nickel-based bifunctional electrocatalyst composed of Co4S3, Co(OH)2, Ni3Se2, and nickel foam (NF) by a hydrothermal method combined with an electrochemical method, and realizes modification and optimization of the original nickel-based catalyst by morphology control and electronic control to improve its intrinsic electrocatalytic activity. The preparation method of the ternary composite nickel-based bifunctional electrocatalyst comprises the following steps:

[0009] S1. Pretreatment of nickel foam (NF): After ultrasonic etching of nickel foam in dilute hydrochloric acid, the nickel foam is rinsed with deionized water and anhydrous ethanol, and vacuum dried to perform pretreatment of nickel foam;

[0010] S2. Hydrothermal synthesis of Ni3Se2 / NF: Add a reducing agent, a cation releasing agent, a selenium source and a nickel salt to a solvent, respectively, stir well to obtain a uniformly dispersed mixed solution, add the NF pretreated in step S1 to carry out the first hydrothermal reaction, and after the reactor is naturally cooled to room temperature, take out the sample, rinse it with deionized water and anhydrous ethanol for several times, and dry it to obtain Ni3Se2 / NF;

[0011] S3, hydrothermal synthesis of Co(OH)2 / Ni3Se2 / NF: cobalt salt, morphology regulator and precipitant were added to the solvent, and Ni3Se2 / NF obtained in step S2 was added to carry out a second hydrothermal reaction. After the reactor was naturally cooled to room temperature, the sample was taken out, rinsed with deionized water and anhydrous ethanol for several times, and dried to obtain Co(OH)2 / Ni3Se2 / NF;

[0012] S4. Electrochemical synthesis of a ternary composite nickel-based bifunctional electrocatalyst: Co(OH)2 / Ni3Se2 / NF was placed in an electrodeposition solution as a working electrode, and an anion exchange reaction was performed on Co(OH)2 / Ni3Se2 / NF by electrochemical treatment to obtain a ternary composite nickel-based bifunctional electrocatalyst, which was recorded as Co4S3 / Co(OH)2 / Ni3Se2 / NF.

[0013] Preferably, in step S1, the size of the nickel foam NF is 1.5×1.0 cm.

[0014] Preferably, the concentration of the dilute hydrochloric acid in step S1 is 2-5 M, and the etching time is 20-40 min.

[0015] Preferably, the solvent in step S2 is one or more of DMF, ethanol and deionized water.

[0016] Preferably, the reducing agent in step S2 is one or more of citric acid, hydrazine hydrate, ammonia water, and NaBH4.

[0017] Preferably, the cation releasing agent in step S2 is one or more of β-cyclodextrin and zeolite.

[0018] Preferably, the selenium source in step S2 is one or more of Se powder, Na2SeO3, and SeO2.

[0019] Preferably, the nickel salt in step S2 is one or more of Ni(NO3)2, NiCl2, and NiSO4.

[0020] Preferably, the molar ratio of the reducing agent, cation releasing agent, selenium source and nickel salt in step S2 is 9:5:2:4.

[0021] Preferably, the usage ratio of the solvent and the selenium source in step S2 is 20 mL:0.1 mmol.

[0022] Preferably, the first hydrothermal reaction in step S2 is carried out in a high pressure reactor, the reaction temperature is 160-200° C., and the reaction time is 14-17 h.

[0023] Preferably, the solvent in step S3 is one or more of DMF, ethanol and deionized water.

[0024] Preferably, the cobalt salt in step S3 is one or more of CoCl2, CoSO4, and Co(NO3)2.

[0025] Preferably, the morphology control agent in step S3 is one or more of ammonium fluoride, sodium citrate and sodium acetate.

[0026] Preferably, the precipitant in step S3 is one or more of urea, KOH and NaOH.

[0027] Preferably, the molar ratio of the cobalt salt, the morphology regulator and the precipitant in step S3 is 2-3:1-2:3-4.

[0028] Preferably, the second hydrothermal reaction in step S3 is carried out in a high pressure reactor, the reaction temperature is 110-140° C., and the reaction time is 6-9 h.

[0029] Preferably, the electrodeposition solution in step S4 includes a pH regulator and a sulfur source.

[0030] Preferably, the pH regulator is one or more of KOH and NaOH, and the sulfur source is one or more of Na2S, K2S, Na2SO4, and K2SO4.

[0031] Preferably, the molar ratio of the pH regulator to the sulfur source in the electrodeposition solution is 2:1 to 2:3, and the concentration of the sulfur source in the electrodeposition solution is 0.5 to 1.5M.

[0032] Preferably, the parameters of the electrochemical treatment in step S4 are: under a standard three-electrode system, using the Cyclic Voltammetry method, the applied voltage scanning range is -0.2 to 1.0 V vs. RHE, the scanning rate is 50 to 100 mV / s, and the number of cycles is 80 to 200.

[0033] Preferably, the three-electrode system is: Co4S3 / Co(OH)2 / Ni3Se2 / NF as the working electrode, Ag / AgCl as the reference electrode, and Pt wire as the counter electrode.

[0034] The present invention also provides the use of the above-mentioned ternary composite nickel-based bifunctional electrocatalyst in the electrolysis of water to produce hydrogen by assisting the oxidation reaction of sulfur ions.

[0035] The present invention provides a ternary composite nickel-based bifunctional electrocatalyst and a preparation method thereof, wherein the electrocatalyst comprises a bottom layer of nickel foam NF as a conductive substrate, and a surface layer covered with in-situ self-grown Ni3Se2, Co(OH)2 and Co4S3, forming a multi-component sandwich structure. The beneficial effects of the present invention are:

[0036] (1) Unique morphology and structure: Fluffy hydroxide intermediates are synthesized through morphology regulation to avoid material clusters, good hydrophilicity and exposed active sites, which promote its electron transfer and mass transfer. In addition, the sandwich structure design greatly protects the inner layer active material from being destroyed and catalyzed, greatly enhancing its reactivity and stability.

[0037] (2) Synergistic effect of ternary composite materials: Through a layer-by-layer synthetic design, the electrochemical impedance of the catalyst is effectively reduced. The electron rearrangement at the heterogeneous interface and the strong coupling effect further reduce the intermediate barrier of the reaction, thereby enhancing the electrocatalytic activity and enabling it to perform well in a variety of electrochemical reactions.

[0038] (3) Finely controlled sulfurization process: The synthesis process of electrochemical sulfurization is highly controllable, and the inner layer Co(OH)2 components are retained during sulfurization, thereby providing more electrochemical active sites, shortening the ion diffusion path, and promoting the electrochemical reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0040] Figure 1 Schematic diagram of the synthesis of Co4S3 / Co(OH)2 / Ni3Se2 / NF in an embodiment of the present invention;

[0041] Figure 2 XRD diagrams of Ni3Se2 / NF, Co(OH)2 / Ni3Se2 / NF, and Co4S3 / Co(OH)2 / Ni3Se2 / NF in Example 1 of the present invention;

[0042] Figure 3 The LSV curves of the electrochemical SOR and HER of Ni3Se2 / NF, Co(OH)2 / Ni3Se2 / NF, and Co4S3 / Co(OH)2 / Ni3Se2 / NF in Example 1 of the present invention are shown, wherein (a) is the LSV curve of SOR, and (b) is the LSV curve of HER;

[0043] Figure 4 CV graphs of Co4S3 / Co(OH)2 / Ni3Se2 / NF at different scan rates in Example 1 of the present invention; (ac) were tested in 1MNaOH electrolyte; (df) were tested in 1M NaOH+1MNa2S electrolyte;

[0044] Figure 5 The electrochemically active surface area (ECSA) diagram is shown in Figure 2, where (a) is the test in 1M NaOH electrolyte; (b) is the test in 1M NaOH+1M Na2S electrolyte.

[0045] Figure 6It is the LSV curve diagram of the SOR / / HER coupling system based on the Co4S3 / Co(OH)2 / Ni3Se2 / NF electrode in Example 1 with 1M NaOH as the cathode electrolyte and 1M NaOH+1M Na2S as the anode electrolyte, and the LSV curve diagram of the OER / / HER coupling system with 1M NaOH as the cathode electrolyte and the anode electrolyte. DETAILED DESCRIPTION

[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0047] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0048] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0049] The nickel foam in the embodiment of the present invention was purchased from Hefei Kejing Material Technology Co., Ltd., with specifications of: length 1000mm*width 300mm*thickness 1.6mm, 3N surface density 350g / m 2 ; Other raw materials are common commercially available products.

[0050] The present invention uses an X-ray diffractometer and a Chenhua 660e electrochemical workstation to characterize and analyze the comparative material prepared in this embodiment.

[0051] Evaluation of SOR and HER performance of the three-electrode system in the embodiment of the present invention:

[0052] (1) SOR electrochemical performance test: The test was carried out on a CHI 660E electrochemical workstation. In the traditional three-electrode system, the synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was 1.00 M NaOH + 1.00 M Na2S;

[0053] In the range of -0.2 to -1.0 V (relative to Ag / AgCl), the -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0054] (2) HER electrochemical performance test: The test was carried out on a CHI 660E electrochemical workstation. In the traditional three-electrode system, the synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was 1.00M NaOH. The HER electrochemical performance was tested at 5mV·s in the range of 1.0-1.6V (relative to Ag / AgCl). -1 The LSV curve was tested at a scan rate of , and 90% impedance compensation was taken to obtain the final LSV curve.

[0055] Catalyst CV test and electrochemically active surface area (ECSA) evaluation in the embodiments of the present invention:

[0056] The test was carried out on a CHI 660E electrochemical workstation. In the traditional three-electrode system, the synthesized catalyst was directly used as the working electrode, the platinum electrode was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was 1.00M NaOH or 1.00M NaOH+1.00M Na2S. -1 , 40mV·s -1 、60mV·s -1 、80mV·s -1 , 100mV·s -1 ) under CV curve. Due to the electrochemical double layer capacitance (C dl ) is closely related to the ECSA and can be estimated by plotting the charge current difference Δj = (ja-jc), where the linear slope fits C dl is twice the scanning rate. Therefore, C dl It can be approximately expressed by the following formula.

[0057] j=S×C dl ×ν

[0058] Where j is half of the double layer capacitance current density (mA cm -2 ), S is the measured area of ​​the electrode (S = 1.0 × 1.0 cm 2 ), ν is the scanning rate (mV·S -1 ).

[0059] Performance evaluation of the two-electrode SOR\\HER and OER\\HER coupling system in the embodiment of the present invention:

[0060] (1) Assembly and testing of SOR\\HER: The test was carried out on a CHI 660E electrochemical workstation, with the prepared catalyst as the working electrode, the platinum electrode as the counter electrode, the catholyte as 1.00 M NaOH, and the anolyte as 1.00 M NaOH + 1.00 M Na2S;

[0061] In the range of 0 to 0.8 V (relative to Ag / AgCl), the -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0062] (2) Assembly and testing of OER\\HER: The test was carried out on a CHI 660E electrochemical workstation, with the prepared catalyst as the working electrode, the platinum electrode as the counter electrode, and 1.00 M NaOH as the cathode and anode electrolytes;

[0063] In the range of 1.2 to 2.0 V (relative to Ag / AgCl), the -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0064] Example 1

[0065] Co4S3 / Co(OH)2 / Ni3Se2 / NF was synthesized as follows:

[0066] (1) Pretreatment of the conductive current collector nickel foam (NF):

[0067] First, the nickel foam was cut into a size of 1.5 × 1.0 cm;

[0068] Subsequently, the cut nickel foam was ultrasonically etched in 3M dilute hydrochloric acid for 30 minutes to remove the oxide layer on the surface;

[0069] After ultrasonic etching, the nickel foam was rinsed several times with deionized water and anhydrous ethanol to ensure that the residual dilute hydrochloric acid was completely removed;

[0070] Finally, the treated nickel foam is dried under vacuum conditions at 60°C to completely remove moisture and prevent it from oxidation, preparing it for subsequent use.

[0071] (2) Hydrothermal synthesis of Ni3Se2 / NF:

[0072] First, 0.25 mmol of β-cyclodextrin was fully dissolved in 20 mL of DMF, and then 0.2 mmol of nickel nitrate, 0.1 mmol of SeO2, and 0.45 mmol of citric acid were added respectively. After stirring for 1 h, a uniformly dispersed mixed solution was obtained.

[0073] Subsequently, the NF pretreated in step (1) was added and transferred to a high-pressure reactor, the hydrothermal temperature was 180°C, and the reaction time was 15 h;

[0074] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Ni3Se2 / NF.

[0075] (3) Hydrothermal synthesis of Co(OH)2 / Ni3Se2 / NF:

[0076] First, 2.4 mmol of cobalt nitrate, 3.7 mmol of urea, and 1.7 mmol of ammonium fluoride were added to 36 mL of deionized water, and a uniformly dispersed mixed solution was obtained after stirring for 30 minutes;

[0077] Subsequently, the precursor obtained in step (2) and the mixed solution were transferred to a high-pressure reactor, the hydrothermal temperature was 120° C., and the reaction time was 8 h;

[0078] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed with deionized water and anhydrous ethanol for several times, and dried at 60°C to obtain Co(OH)2 / Ni3Se2 / NF.

[0079] (4) Electrochemical synthesis of Co4S3 / Co(OH)2 / Ni3Se2 / NF:

[0080] First, 1M Na2S + 1M NaOH was used as the electrodeposition solution, and in a standard three-electrode system (the three-electrode system is: Ni3Se2 / NF as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode), the Cyclic Voltammetry method was used, the applied voltage scanning range was -0.2 to 1.0 V vs. RHE, the scanning rate was 50 mV / s, and the number of cycles was 160;

[0081] Subsequently, the deposited samples were rinsed with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Co4S3 / Co(OH)2 / Ni3Se2 / NF.

[0082] Depend on Figure 2 The XRD pattern shows that the sample Co4S3 / Co(OH)2 / Ni3Se2 / NF corresponds well to the standard card, indicating the successful synthesis of the ternary composite Co4S3 / Co(OH)2 / Ni3Se2 / NF. Figure 3 From the LSV curves, it can be seen that Co4S3 / Co(OH)2 / Ni3Se2 / NF has excellent electrochemical activity, and only overpotentials of 0.175 V and 0.298 V are required to reach 100 mA cm in HER and SOR, respectively. -2 Current density. Figure 5From the ECSA, it can be seen that Co4S3 / Co(OH)2 / Ni3Se2 / NF has the largest electrochemical active surface area (318.67 mF·cm) in both 1M Na2S+1M NaOH (anode) and 1M NaOH electrolyte (cathode). -2 and 372.31mF·cm -2 ), which indicates that Co4S3 / Co(OH)2 / Ni3Se2 / NF not only possesses compatible SOR and HER electrocatalytic active sites in SOR and HER reactions, but also has more surface active sites, which is beneficial to improve its intrinsic activity and thus optimize the adsorption / desorption of reactants on the catalytic surface.

[0083] Constructing a three-electrode system to evaluate the electrocatalytic performance of the catalyst:

[0084] The electrocatalytic SOR and HER performance of Ni3Se2 / NF, Co(OH)2 / Ni3Se2 / NF and Co4S3 / Co(OH)2 / Ni3Se2 / NF prepared in Example 1 were tested at 100 mA·cm -2 The overpotential under current density is used as the catalyst activity evaluation standard. The LSV curves of electrochemical SOR and HER of Co4S3 / Co(OH)2 / Ni3Se2 / NF and the examples are shown in Figure 3 .Depend on Figure 3 It can be seen that the electrocatalytic activity of Co(OH)2 / Ni3Se2 / NF is significantly better than that of Ni3Se2 / NF, indicating that the design of the heterostructure effectively optimizes the electron rearrangement at the interface. However, the electrocatalytic activity of the two-phase heterostructure Co(OH)2 / Ni3Se2 / NF is still unsatisfactory. The catalyst was synthesized by an easy-to-control electrochemical sulfurization method, which effectively retained the inner layer Co(OH)2 from being completely sulfurized, and then finely regulated the charge transfer. The strong interface coupling effect made the electrocatalytic activity of the catalyst progressive layer by layer, and finally designed a three-layer composite Co4S3 / Co(OH)2 / Ni3Se2 / NF with excellent electrocatalytic activity. In addition, Co4S3 / Co(OH)2 / Ni3Se2 / NF not only responds well to the SOR reaction, but also has excellent HER activity, indicating that the catalyst prepared by the present invention has significant advantages over conventional catalysts in the field of sulfur ion purification and hydrogen production, and can effectively reduce the energy input required for electrocatalysis, thereby realizing an energy-saving desulfurization and hydrogen production strategy, which meets the dual needs of the times and green chemistry.

[0085] Electrochemically active site ECSA exploration:

[0086] Since the electrochemical double layer capacitance (Cdl) is closely related to ECSA, the Figure 4 The electrochemical active surface area was calculated by CV at different scan rates. Figure 5It can be seen that Co4S3 / Co(OH)2 / Ni3Se2 / NF has the largest electrochemical active surface area in both SOR and HER reactions, followed by Co(OH)2 / Ni3Se2 / NF and Ni3Se2 / NF. This shows that the design of the three-layer composite structure not only provides abundant active sites through a layer-by-layer progressive approach, but also promotes the contact between the catalyst surface and the electrolyte, thereby effectively improving the electrocatalytic activity.

[0087] Evaluation of electrocatalytic performance of two-electrode system:

[0088] Depend on Figure 6 It can be obtained that the SOR\\HER system is at 100mA·cm -2 The overpotential under current density is only 0.59V, while that of OER\\HER system is 1.96V. The SOR\\HER system saves about 70% of energy consumption. It can be seen that using bifunctional Co4S3 / Co(OH)2 / Ni3Se2 / NF as both cathode and anode catalysts of SOR\\HER system not only achieves hydrogen production while purifying sulfur-containing waste gas, but also significantly reduces energy consumption. This not only highlights the energy, economic and environmental benefits of multifunctional catalysts, but also provides solid theoretical support and practical basis for innovation and optimization in the field of catalysis.

[0089] Example 2

[0090] Co4S3 / Co(OH)2 / FeSe2 / NF was synthesized as follows:

[0091] (1) Pretreatment of the conductive current collector nickel foam (NF): same as in Example 1.

[0092] (2) Hydrothermal synthesis of FeSe / NF precursor:

[0093] First, 0.25 mmol of β-cyclodextrin was fully dissolved in 20 mL of DMF, and then 0.2 mmol of ferric nitrate, 0.1 mmol of SeO2, and 0.45 mmol of citric acid were added respectively. After stirring for 1 h, a uniformly dispersed mixed solution was obtained.

[0094] Subsequently, the NF pretreated in step (1) was added and transferred to a high-pressure reactor, the hydrothermal temperature was 180°C, and the reaction time was 15 h;

[0095] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain the FeSe / NF precursor.

[0096] (3) Hydrothermal synthesis of Co(OH)2 / FeSe / NF:

[0097] First, 2.4 mmol of cobalt nitrate, 3.7 mmol of urea, and 1.7 mmol of ammonium fluoride were added to 36 mL of deionized water, and a uniformly dispersed mixed solution was obtained after stirring for 30 minutes;

[0098] Subsequently, the precursor obtained in step (2) and the mixed solution were transferred to a high-pressure reactor, the hydrothermal temperature was 120° C., and the reaction time was 8 h;

[0099] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain the Co(OH)2 / FeSe / NF precursor.

[0100] (4) Electrochemical synthesis of Co4S3 / Co(OH)2 / FeSe / NF:

[0101] First, 1M Na2S+1M NaOH was used as the electrodeposition solution, and in a standard three-electrode system (the three-electrode system was: Co(OH)2 / FeSe / NF as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode), the Cyclic Voltammetry method was used, the applied voltage scanning range was -0.2 to 1.0 V vs. RHE, the scanning rate was 50 mV / s, and the number of cycles was 160;

[0102] Subsequently, the deposited samples were rinsed with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Co4S3 / Co(OH)2 / FeSe / NF.

[0103] Example 3

[0104] Co4S3 / Co(OH)2 / CuSe / NF was synthesized as follows:

[0105] (1) Pretreatment of the conductive current collector nickel foam (NF): same as in Example 1.

[0106] (2) Hydrothermal synthesis of CuSe / NF precursor:

[0107] First, 0.25 mmol of β-cyclodextrin was fully dissolved in 20 mL of DMF, and then 0.2 mmol of copper sulfate, 0.1 mmol of SeO2, and 0.45 mmol of citric acid were added respectively. After stirring for 1 h, a uniformly dispersed mixed solution was obtained.

[0108] Subsequently, the NF pretreated in step (1) was added and transferred to a high-pressure reactor, the hydrothermal temperature was 180°C, and the reaction time was 15 h;

[0109] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60° C. to obtain the CuSe / NF precursor.

[0110] (3) Hydrothermal synthesis of Co(OH)2 / CuSe / NF precursor:

[0111] First, 2.4 mmol of cobalt nitrate, 3.7 mmol of urea, and 1.7 mmol of ammonium fluoride were added to 36 mL of deionized water, and a uniformly dispersed mixed solution was obtained after stirring for 30 minutes;

[0112] Subsequently, the precursor obtained in step (2) and the mixed solution were transferred to a high-pressure reactor, the hydrothermal temperature was 120° C., and the reaction time was 8 h;

[0113] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain the Co(OH)2 / CuSe / NF precursor.

[0114] (4) Electrochemical synthesis of Co4S3 / Co(OH)2 / CuSe / NF:

[0115] First, 1M Na2S + 1M NaOH was used as the electrodeposition solution, and in a standard three-electrode system (the three-electrode system is: Co(OH)2 / CuSe / NF as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode), the Cyclic Voltammetry method was used, the applied voltage scanning range was -0.2 to 1.0 V vs. RHE, the scanning rate was 50 mV / s, and the number of cycles was 160;

[0116] Subsequently, the deposited samples were rinsed with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Co4S3 / Co(OH)2 / CuSe / NF.

[0117] Example 4

[0118] Co4S3 / Co(OH)2 / CoSe / NF was synthesized as follows:

[0119] (1) Pretreatment of the conductive current collector nickel foam (NF): same as in Example 1.

[0120] (2) Hydrothermal synthesis of CoSe / NF precursor:

[0121] First, 0.25 mmol of β-cyclodextrin was fully dissolved in 20 mL of DMF, and then 0.2 mmol of cobalt nitrate, 0.1 mmol of SeO2, and 0.45 mmol of citric acid were added respectively. After stirring for 1 h, a uniformly dispersed mixed solution was obtained.

[0122] Subsequently, the NF pretreated in step (1) was added and transferred to a high-pressure reactor, the hydrothermal temperature was 180°C, and the reaction time was 15 h;

[0123] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60° C. to obtain the CoSe / NF precursor.

[0124] (3) Hydrothermal synthesis of Co(OH)2 / CoSe / NF precursor:

[0125] First, 2.4 mmol of cobalt nitrate, 3.7 mmol of urea, and 1.7 mmol of ammonium fluoride were added to 36 mL of deionized water, and a uniformly dispersed mixed solution was obtained after stirring for 30 minutes;

[0126] Subsequently, the precursor obtained in step (2) and the mixed solution were transferred to a high-pressure reactor, the hydrothermal temperature was 120° C., and the reaction time was 8 h;

[0127] Finally, after the reactor was naturally cooled to room temperature, the sample was taken out, rinsed several times with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain the Co(OH)2 / CoSe / NF precursor.

[0128] (4) Electrochemical synthesis of Co4S3 / Co(OH)2 / CoSe / NF:

[0129] First, 1M Na2S + 1M NaOH was used as the electrodeposition solution, and in a standard three-electrode system (the three-electrode system is: Co(OH)2 / CoSe / NF as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode), the Cyclic Voltammetry method was used, the applied voltage scanning range was -0.2 to 1.0 V vs. RHE, the scanning rate was 50 mV / s, and the number of cycles was 160;

[0130] Subsequently, the deposited samples were rinsed with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Co4S3 / Co(OH)2 / CoSe / NF.

[0131] Evaluation of electrocatalytic performance of three-electrode system:

[0132] The electrocatalytic SOR and HER performance of Examples 1-4 were tested at 100 mA cm -2 The overpotential under current density was used as the evaluation standard for catalyst activity, and the results are shown in Table 1.

[0133] Table 1

[0134]

[0135] It can be seen that the electrocatalytic activity of iron-based, copper-based and cobalt-based catalysts is not good, and their performance is not enough to meet the requirements of energy-saving hydrogen production technology by sulfide ion oxidation-assisted water electrolysis. The performance of the nickel-based ternary catalyst in Example 1 is much better than these three catalysts, which is attributed to the unique interface effect of the nickel-based catalyst and the simultaneous presence of soft acid and hard acid sites therein, which synergistically promote the electrocatalytic activity.

[0136] Example 5

[0137] The following steps were used to synthesize Co4S3 / Co(OH)2 / Ni3Se2 / NF-80 with 80 cycles of electrochemical sulfurization:

[0138] (1) Pretreatment of the conductive current collector nickel foam: same as in Example 1.

[0139] (2) Hydrothermal synthesis of Ni3Se2 / NF: Same as Example 1.

[0140] (3) Hydrothermal synthesis of Co(OH)2 / Ni3Se2 / NF precursor: same as Example 1.

[0141] (4) Electrochemical synthesis of Co4S3 / Co(OH)2 / Ni3Se2 / NF-80:

[0142] First, 1M Na2S+1M NaOH was used as the electrodeposition solution, and in a standard three-electrode system (the three-electrode system is: Co(OH)2 / Ni3Se2 / NF as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode), the Cyclic Voltammetry method was used, the applied voltage scanning range was -0.2 to 1.0 V vs. RHE, the scanning rate was 50 mV / s, and the number of cycles was 80;

[0143] Subsequently, the deposited samples were rinsed with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Co4S3 / Co(OH)2 / Ni3Se2 / NF-80.

[0144] Example 6

[0145] The following steps were used to synthesize Co4S3 / Co(OH)2 / Ni3Se2 / NF-320 with 320 cycles of electrochemical sulfurization:

[0146] (1) Pretreatment of the conductive current collector nickel foam: same as in Example 1.

[0147] (2) Hydrothermal synthesis of Ni3Se2 / NF: Same as Example 1.

[0148] (3) Hydrothermal synthesis of Co(OH)2 / Ni3Se2 / NF precursor: same as Example 1.

[0149] (4) Electrochemical synthesis of Co4S3 / Co(OH)2 / Ni3Se2 / NF-320:

[0150] First, 1M Na2S + 1M NaOH was used as the electrodeposition solution, and in a standard three-electrode system (the three-electrode system is: Co(OH)2 / Ni3Se2 / NF as the working electrode, Ag / AgCl as the reference electrode, and platinum wire as the counter electrode), the Cyclic Voltammetry method was used, the applied voltage scanning range was -0.2 to 1.0 V vs. RHE, the scanning rate was 50 mV / s, and the number of cycles was 320;

[0151] Subsequently, the deposited samples were rinsed with deionized water and anhydrous ethanol, respectively, and dried at 60°C to obtain Co4S3 / Co(OH)2 / Ni3Se2 / NF-320.

[0152] Evaluation of electrocatalytic performance of three-electrode system:

[0153] The electrocatalytic SOR and HER performance of Examples 5-6 were tested at 100 mA cm -2 The overpotential under current density was used as the evaluation standard for catalyst activity, and the results are shown in Table 2.

[0154] Table 2

[0155]

[0156] As can be seen from Table 2, the HER and SOR performances of the samples with different numbers of electrochemical sulfurization cycles in the comparative example are not good, which is due to the inappropriate degree of electrochemical sulfurization. Insufficient sulfurization will result in the sample having Co4S3 only on the surface, which cannot further protect the inner layer active material, resulting in poor electrocatalytic performance of the sample. Excessive sulfurization will weaken the electronic coupling force between the multilayer heterostructure of the sample and reduce the electron transfer rate, resulting in poor electrocatalytic activity of the sample. It can be seen that the fine control of the sample by reasonable electrochemical sulfurization can achieve the most favorable heterogeneous interface electron rearrangement, thereby adjusting the electrocatalytic active center and reducing the reaction energy barrier, so that the sample has the best electrocatalytic activity.

[0157] In summary, in view of the long-standing problems in the past such as insufficient electrocatalytic activity of nickel-based catalysts, difficulty in synthesizing multi-component heterogeneous structural materials, and uncontrollable traditional hydrothermal synthesis, the present invention effectively improves the electrocatalytic activity of the catalyst from the following two aspects: (1) A layer-by-layer progressive structural design is adopted to synthesize a bifunctional electrocatalyst integrating different compatible active sites, thereby effectively enhancing the reaction kinetics of the catalyst and thus enhancing the electrocatalytic activity; (2) Through the fine regulation of electrochemical sulfurization, the inner layer Co(OH)2 structure is effectively retained, further promoting the rearrangement of electrons at the heterogeneous interface, effectively optimizing the electrocatalytic active center, and thus improving the electrocatalytic activity of the catalyst.

[0158] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A ternary composite nickel-based bifunctional electrocatalyst, characterized in that: The electrocatalyst comprises a bottom layer of foamed nickel as a conductive substrate, and a surface layer covered with in-situ self-grown Ni3Se2, Co(OH)2 and Co4S3, forming a multi-component sandwich structure.

2. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 1, characterized in that: The following steps are involved: S1. Pretreatment of nickel foam: ultrasonically etch the nickel foam in dilute hydrochloric acid, then wash and dry it; S2. Hydrothermal synthesis of Ni3Se2 / NF: Add a reducing agent, a cation releasing agent, a selenium source and a nickel salt to a solvent, respectively, stir well to obtain a uniformly dispersed mixed solution, add the nickel foam pretreated in step S1 to carry out the first hydrothermal reaction, and after the reactor is naturally cooled to room temperature, take out the sample, wash it, and dry it to obtain Ni3Se2 / NF; S3, hydrothermal synthesis of Co(OH)2 / Ni3Se2 / NF: cobalt salt, morphology regulator and precipitant were added to the solvent to carry out a second hydrothermal reaction on Ni3Se2 / NF. After the reactor was cooled to room temperature naturally, the sample was taken out, washed and dried to obtain Co(OH)2 / Ni3Se2 / NF. S4. Electrochemical synthesis of ternary composite nickel-based bifunctional electrocatalyst: Co(OH)2 / Ni3Se2 / NF is placed in an electrodeposition solution as a working electrode, and an anion exchange reaction is performed on Co(OH)2 / Ni3Se2 / NF through electrochemical treatment to obtain a ternary composite nickel-based bifunctional electrocatalyst.

3. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: In step S1, the concentration of the dilute hydrochloric acid is 2-5 M, and the etching time is 20-40 min.

4. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: The solvent in step S2 is one or more of DMF, ethanol, and deionized water; And / or, the reducing agent in step S2 is one or more of citric acid, hydrazine hydrate, ammonia water, and NaBH4; And / or, the cation releasing agent in step S2 is one or more of β-cyclodextrin and zeolite; And / or, the selenium source in step S2 is one or more of Se powder, Na2SeO3, and SeO2. And / or, the nickel salt in step S2 is one or more of Ni(NO3)2, NiCl2, and NiSO4. And / or, the molar ratio of the reducing agent, the cation releasing agent, the selenium source and the nickel salt in step S2 is 9:5:2:

4. The usage ratio of the solvent and the selenium source in step S2 is 20 mL:0.1 mmol.

5. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: The first hydrothermal reaction in step S2 is carried out in a high pressure reactor, the reaction temperature is 160-200° C., and the reaction time is 14-17 hours.

6. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: The solvent in step S3 is one or more of DMF, ethanol, and deionized water; And / or, the cobalt salt in step S3 is one or more of CoCl2, CoSO4, and Co(NO3)2; And / or, the morphology control agent in step S3 is one or more of ammonium fluoride, sodium citrate, and sodium acetate; And / or, the precipitant in step S3 is one or more of urea, KOH, and NaOH; And / or, the molar ratio of the cobalt salt, the morphology regulating agent, and the precipitant in step S3 is 2-3:1-2:3-4.

7. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: The second hydrothermal reaction in step S3 is carried out in a high pressure reactor, the reaction temperature is 110-140° C., and the reaction time is 6-9 hours.

8. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: The electrodeposition solution in step S4 includes a pH regulator and a sulfur source; The pH regulator is one or more of KOH and NaOH, and the sulfur source is one or more of Na2S, K2S, Na2SO4, and K2SO4; The molar ratio of the pH regulator to the sulfur source in the electrodeposition solution is 2:1 to 2:3, and the concentration of the sulfur source in the electrodeposition solution is 0.5 to 1.5M.

9. The method for preparing the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 2, characterized in that: The parameters of the electrochemical treatment in step S4 are: under a standard three-electrode system, using the Cyclic Voltammetry method, the applied voltage scanning range is -0.2 to 1.0 V vs. RHE, the scanning rate is 50 to 100 mV / s, and the number of cycles is 80 to 200; The three-electrode system comprises: a ternary composite nickel-based bifunctional electrocatalyst as a working electrode, Ag / AgCl as a reference electrode, and a platinum wire as a counter electrode.

10. Use of the ternary composite nickel-based bifunctional electrocatalyst as claimed in claim 1 in the electrolysis of water to produce hydrogen assisted by sulfide ion oxidation reaction.

Citation Information

Patent Citations

  • Foamed nickel loaded sulfide electrocatalyst as well as preparation method and application thereof

    CN112962115A

  • Preparation method of Co4S3 / Ni3S2 / Ni (OH) 2 three-phase heterojunction catalyst and application of Co4S3 / Ni3S2 / Ni (OH) 2 three-phase heterojunction catalyst in hydrogen production

    CN118480812A

  • Preparation method and application of Mo-doped Cu2S / Ni3S2 / NF composite material with heterostructure

    CN118895527A

  • Self-standing BI-functional electrode for overall water electrolysis

    WO2024189651A1